2021
DOI: 10.3389/fmars.2021.806450
|View full text |Cite|
|
Sign up to set email alerts
|

Transport and Fate of 137Cs Released From Multiple Sources in the North Atlantic and Arctic Oceans

Abstract: The North Atlantic and Arctic oceans, along with the North Pacific, are the main reservoirs of anthropogenic radionuclides introduced in the past 75 years. The POSEIDON-R compartment model was applied to the North Atlantic and Arctic oceans to reconstruct 137Cs contamination in 1945–2020 due to multiple sources: global fallout, exchange flows with other oceans, point-source inputs in the ocean from reprocessing plants and other nuclear facilities, the impact of the Chernobyl accident and secondary contaminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The outflowing Chernobyl-derived 137 Cs from the Baltic Sea has been observed in the Skagerrak and along the Norwegian coast (Povinec et al, 2003). The modeling results indicated that the outflux from the North Sea has persistent contribution (even though less important than those from global fallout and nuclear reprocessing plants) to the 137 Cs in the Northern North Sea and the Norwegian Sea since the 1990 s (Maderich et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…The outflowing Chernobyl-derived 137 Cs from the Baltic Sea has been observed in the Skagerrak and along the Norwegian coast (Povinec et al, 2003). The modeling results indicated that the outflux from the North Sea has persistent contribution (even though less important than those from global fallout and nuclear reprocessing plants) to the 137 Cs in the Northern North Sea and the Norwegian Sea since the 1990 s (Maderich et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…However, it is believed that larger effects were observed in the vicinity of Chernobyl than those observed in Japan. The fallout into the marginal sea of Europe, including the Black Sea, Mediterranean Sea, and North Sea, was large, while the fallout into the North Atlantic was small (Maderich et al, 2021). In this comparison, the marginal sea was excluded from consideration because an ocean general circulation model with a resolution of 1 • was used.…”
Section: Other Sourcesmentioning
confidence: 99%
“…The effect of the Chernobyl accident can be seen, although this setting was based on fallout data from the location of the MRI in Japan and was not accurate. The impact of the Chernobyl accident in the North Atlantic was small, however the impact on the Baltic Sea and other marginal sea was significant (Maderich et al, 2021). The impact of outflows from the Baltic Sea to the North Atlantic was not considered in this study and is a subject for future work.…”
Section: Inventorymentioning
confidence: 99%
“…Consequently, monitoring programs and research studies have been giving priority for Cs-137 activity concentrations, trends, and concentration factors in contaminated areas. For example, Cs-137 analysis and accumulation monitoring in edible fishes and marine wildlife have been given great attention in Japan, 6 the European Union, 7 , 8 and U.K. 9 Regulators and stakeholders make use of concentration factors and the derived concentration guideline levels for calculations of regulated discharges. Therefore, Cs-137 monitoring in seawater is important for decision-making and for supporting disposal programs.…”
mentioning
confidence: 99%